Humid mesothermal climate and open forest at the early Miocene Landslip Hill deposit (Gore Lignite Measures), Southern Zealandia - Tammo Reichgelt; Joseph A. Jackson; John G. Conran; Christopher K. West; Elizabeth M. Kennedy; Daphne E. Lee (Earth History and Biodiversity)
Plant fossils at the southern Zealandia Landslip Hill deposit (early Miocene, Gore Lignite Measures) are preserved in a silcrete matrix and reveal unique three-dimensional structures. Here, we present fossil leaf-based paleoclimate and vegetation reconstructions, as well as a comparison of the diversity at the site to modern New Zealand forests. The early Miocene climate at the site is much warmer than modern (mean annual temperature 17.6 ± 2.3 °C versus ∼10 °C today), but with similar annual precipitation rates (96 +67/-39 cm yr−1 versus ∼100 cm yr−1 today). Temperature seasonality is similar to today, whereas the locality experienced stronger precipitation seasonality, likely due to the southward migration of the moisture-laden westerly wind belt during early Miocene summers. The reconstructed vegetation at Landslip Hill does not tend towards resource retention strategies, like modern dense evergreen climax forest that exists under similar temperature and precipitation combinations in Zealandia today. Instead, the vegetation includes elements of open vegetation, with nearest living relatives of taxa identified at the site being notable post-disturbance taxa, such as Gleicheniaceae and Casuarinaceae. This indicates that the vegetation at Landslip Hill may have been periodically disturbed, potentially by floods, fire or both. Flood disturbance aligns well with the coarse sandstone facies of the deposit, and the lack of planar bedding in which the fossils are found. However, fire disturbance aligns well with the summer-dry conditions at the site. Overall dicot leaf diversity at Landslip Hill is similar to that of modern New Zealand forests, even those at the same depositional latitude (∼45–46°S); however, unlike modern New Zealand forests, there is no clear dominance of a single taxon.